Acute promyelocytic leukemia with a novel TTMV::RARA fusion initially presenting as vertebral myeloid sarcoma: a case report - Ruijia, Li; Qianqian, Zhang; Xiaohong, Li; Sen, Yang; Nan, Zhang; Jing, Li (Frontiers in Oncology, 2026)
BackgroundAcute promyelocytic leukemia (APL) caused by the TTMV::RARA fusion gene is extremely rare, with fewer than 10 formally reported cases worldwide, and routine molecular tests often fail to detect it. This case is unique because the disease first manifested as vertebral myeloid sarcoma. Although bone marrow morphology and immunophenotyping strongly suggested APL, routine diagnostic methods could not confirm the disease, and the final diagnosis relied on whole- transcriptome sequencing.Case summaryA 39- year- old man was admitted for persistent lower back pain and limited movement of the left lower limb. Imaging revealed destruction of the T9 vertebral body with paravertebral and mediastinal soft- tissue masses. Pathology of the resected mass confirmed myeloid sarcoma. The patient developed pancytopenia and coagulopathy. Bone marrow morphology and flow cytometry showed classic features of APL, and all- trans retinoic acid (ATRA) induction therapy was initiated. However, PML:: RARA PCR and RARa FISH were negative, fusion gene screening and karyotyping found no abnormalities, and the diagnosis was revised to AML, prompting a switch to IA chemotherapy. As the diagnosis remained unclear, whole- transcriptome sequencing was performed and revealed a TTMV::RARA fusion, which was confirmed by RT- PCR. The patient was ultimately diagnosed with TTMV::RARA APL. He later discontinued treatment and died months afterward.ConclusionThis report presents a rare adult case of TTMV::RARA acute promyelocytic leukemia presenting as vertebral myeloid sarcoma. Whole-transcriptome sequencing was essential for diagnosis after routine molecular tests were negative, highlighting the importance of considering rare RARA fusions in APL-like cases lacking PML::RARA. TTMV::RARA APL may be sensitive to ATRA/ATO-based therapy; however, the patient discontinued treatment. Further cases and clinical experience are needed to optimize management strategies for this rare APL subtype.